Proinflammatory transcriptomic and kinomic alterations in astrocytes derived from patients with familial Alzheimer's disease - Benjamin Siciliano; Nicholas D. Henkel; William G. Ryan V; Ali Sajid Imami; John M. Vergis; Chongchong Xu; Taylen O. Arvay; Smita Sahay; Priyanka Pulvender; Abdul-rizaq Hamoud; Chadwick Hales; Robert E. McCullumsmith; et al. (Brain, Behavior, & Immunity - Health, 2025)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder characterized by profound neuronal and cognitive decline, with increasing evidence implicating astrocyte dysfunction in disease pathology. While traditional therapeutic approaches have primarily targeted neurons, the crucial role of astrocytes in metabolism, neurotransmission, amyloid-beta clearance, and neuroinflammation underscores their potential as therapeutic targets. In this study, we employed a multiomic integrative analysis combining transcriptomic and kinomic profiling of human induced pluripotent stem cell (hiPSC)-derived astrocytes from patients with familial AD (fAD) compared to healthy controls (HCs). Our transcriptomic analysis identified 1249 significantly differentially expressed genes, highlighting a pronounced upregulation of inflammatory genes (SERPINA3, IL6R, IL1RAP, TNFRSF11A) and a concomitant downregulation of genes essential for synaptic support and ion channel function (STMN2, NMNAT2, SCN2A, GRIN1). Kinomic profiling revealed dysregulated kinase activities within DYRK, GSK, and MAPK families, further implicating altered kinase signaling pathways in astrocyte dysfunction. Integration of these datasets pinpointed critical molecular hubs, notably within the PI3K signaling and inflammatory pathways, highlighting targets such as JAK2, STAT3, and AKT1 as potential modulators of disease progression. Furthermore, leveraging the Library of Integrated Network-Based Cellular Signatures (LINCS) platform, we identified chemical perturbagens, including fluticasone propionate and Akt inhibitors, capable of reversing the transcriptomic signatures associated with fAD astrocytes. This integrative multiomic approach not only enhances our understanding of astrocyte-specific molecular mechanisms in AD but also provides novel targets for therapeutic intervention aimed at mitigating astrocyte-driven neurodegeneration.